Author Correction: Scutoids are a geometrical solution to three-dimensional packing of epithelia. Issue 1 (December 2018) - Gómez-Gálvez, Pedro; Vicente-Munuera, Pablo; Tagua, Antonio; Forja, Cristina; Castro, Ana; Letrán, Marta; Valencia-Expósito, Andrea; Grima, Clara; Bermúdez-Gallardo, Marina; Serrano-Pérez-Higueras, Óscar; Cavodeassi, Florencia; Sotillos, Sol; et al.
The original version of this Article contained an error in ref. 39, which incorrectly cited 'Fristrom, D. & Fristrom, J. W. in The Development of Drosophila melanogaster (eds. Bate, M. & Martinez-Arias, A.) II, (Cold spring harbor laboratory press, 1993)'. The correct reference is 'Condic, M.L, Fristrom, D. & Fristrom, J.W. Apical cell shape changes during Drosophila imaginal leg disc elongation: a novel morphogenetic mechanism.Development 111 : 23-33 (1991)'. Furthermore, the last sentence of the fourth paragraph of the introduction incorrectly omitted citation of work by Rupprecht et al. The correct citation is given below. These errors have now been corrected in both the PDF and HTML versions of the Article. Rupprecht, J.F., Ong, K.H., Yin, J., Huang, A., Dinh, H.H., Singh, A.P., Zhang, S., Yu, W. & Saunders, T.E. Geometric constraints alter cell arrangements within curved epithelial tissues. Mol. Biol. Cell 28, 3582-3594 (2017).